Setting (on) Fire: Reply to Discussions. Issue 3 (3rd July 2019) - Butler, Daniel G.
ABSTRACT: The author begins by turning to a recent confrontation with four men who chanted homophobic slurs in his neighborhood. He uses this experience to state some of his ideas regarding violence and the setting. Visceral belonging is considered a problem insofar as it is tethered to a setting that constitutively excludes Blackness and queerness in structurally precise ways. Intervention into the setting is theorized as a temporal movement, and the fire of such intervention is couched as a tension of opening and a willingness to burn.